Response on Growth of Oil Palm Seedling (Elaeis guineensis Jacq.) by Adding Dolomite, Fertilizer and Sulphate Reduction Bacteria on Acid Sulphate Soils in Green House - Muhammad Ramadhan; Asmarlaili Sahar Hanafiah; Hardy Guchi (Universitas Sumatera Utara, 2018)
Soil fertility is an important aspect of increasing the growth of oil palm seedling. This research aimed to determine the effect of dolomite, fertilizer and sulphate reduction bacteria (SRB) on the growth of oil palm seedlings. This research was conducted at green house used acid sulphate soils. The research used Randomized Block Design with 3 treatments : Dolomite (without dolomite, dolomite 15,80 tonnes/ha, dolomite 31,60 tonnes/ha), fertilizers (without fertilizer, fertilizer 2,5 grams/seedling, fertilizer 5 grams/seedling) and sulphate reduction bacteria (without SRB and given SRB) with 3 replications. The results showed that the application of dolomite (15,8 and 31,6 tonnes/ha) increased soil pH (4.90 and 4.78) statistically significant. Application of sulphate reduction bacteria increased soil pH (4,59) statistically significant. Application of fertilizers (2,5 and 5 grams/seedling) increased the plant height (40,19 and 44,59 cm) and stem diameter (25,33 and 26,90 mm) statistically significant. Application of dolomite and sulphate reduction bacteria inoculum could increase the plant height and stem diameter of oil palm seedlings more than control. The application of dolomite, fertilizers and also sulphate reduction bacteria inoculum could increase the plant height and stem diameter of oil palm seedlings more than control. The best treatment was dolomite 31,60 tonnes/ha, fertilizer 5 grams/seedling and sulphate reduction bacteria inoculum. Application of dolomite could be replaced with sulphate reduction bacteria inoculum. Keywords : Acid Sulphate Soil, Dolomite, Fertilizer, Soil Fertility, Sulphate Reduction Bacteria